"Occipital Tunnel" Sign on FDG PET for Differentiating Dementias. (February 2018) - Sawyer, David M.; Kuo, Phillip H.
Abstract : Abstract: PET using FDG is a critical tool for evaluation of dementias, with characteristic patterns of hypometabolism suggesting specific diagnoses. Hypometabolism in the occipital region is recognized as an important finding associated with dementia with Lewy bodies and posterior cortical atrophy. We describe here the novel "occipital tunnel" sign, which results from relative sparing of FDG uptake in the medial occipital (primary visual) cortex compared with more severe loss in the surrounding lateral occipital (visual association) cortex. This sign is useful for recognizing the occipital findings of dementia with Lewy bodies and posterior cortical atrophy, especially when viewing sagittal projections.